China doll a play - Mamet, David 1947- (Theatre Communications Group, 2015)
"This complex new work from celebrated playwright David Mamet revolves around a wealthy man, his young fiancée, and an airplane. The man has just bought a new plane as a wedding present for the girl. He intends to go into semiretirement and enjoy himself. While in the process of leaving his office, and giving last minute instructions to his young assistant, he takes one final phone call." --